Influence of Product Quality, Price, and Promotion on Gacoan Noodle Consumers’ Purchase Decisions (Ngagel Surabaya) - Yuweldi Azhari; Dian Ferriswara; Sarwani Sarwani; Galuh Ajeng Ayuningtiyas (Dinamika Publik: Jurnal Manajemen dan Administrasi Bisnis, 2025)
This study investigates the impact of product quality, price, and promotion on consumer purchasing decisions at Mie Gacoan, Ngagel branch, Surabaya. A quantitative research design was adopted, utilizing a survey method with purposive sampling targeting consumers who had made at least one purchase within the previous three months. Following Hair et al.’s recommendation of using ten times the number of measurement indicators, a total of 150 respondents were selected. Data were collected using structured questionnaires encompassing variables related to product quality, price, promotion, and purchasing decisions, and were analyzed using multiple linear regression with SPSS software. The findings reveal that product quality, price, and promotion all exert significant individual and simultaneous effects on purchasing decisions, with a coefficient of determination (R²) of 0.911. Among these factors, promotion demonstrated the strongest influence, followed by product quality and price. These results underscore the critical role of innovative promotional strategies, particularly those leveraging digital and social media platforms, in shaping the purchasing behavior of young consumers, who represent the predominant customer segment. Additionally, maintaining consistent product quality and ensuring competitive pricing remain key to fostering consumer trust and encouraging repeat purchases. The study recommends that Mie Gacoan enhance promotional innovation, sustain product quality standards, and implement competitive pricing strategies to strengthen its market position. Future research should integrate customer satisfaction and loyalty as additional variables and adopt advanced analytical approaches, such as Structural Equation Modeling (SEM), to capture the complexity of consumer behavior dynamics in the fast-food industry more comprehensively.